Antiphospholipide antibodies subtypes in systemic lupus erythematosus and antiphospholipid syndrome - T M Reshetnyak; J Zabek; Z S Alekberova; E N Alexandrova; B Voytsehovskaya (Научно-практическая ревматология)
Objective. То study frequency and clinical significance of different antiphospholipid antibodies (APHLA): anti- cardiolipin (АСА), anti-?2 glycoprotein (AB2), anti-annexin V (AAV) and autoantibodies to oxidized low density lipoproteins (AOLDPL) in pts with systemic lupus erythematosus (SLE) with and without antiphospholipid syndrome (APS). Material and methods. 68 pts (14 male, 54 female, mean age 35,2+11,4 years) followed up in the Institute оГ Rheumatology were included. 45 of them had SLE and 23 - primary APS. 24 from 45 SLE pts had signs of APS. Only instrumentally verified thromboembolic events were recorded. 43 from 68 (63,2%) pts had history of thrombosis. АСА, AB2, AAV and AOLDPL serum level was examined with immuno-enzyme assay. IgG АСА level was in the Institute of Rheumatology of RAMS and in the Institute of Rfeumatology of Warsaw. Lupus anticoagulant was tested with phospholipids-dependent method in platelet depleted plasma. Results. IgG АСА were more frequently revealed in the Institute of Rheumatology of RAMS and were associated with the presence of APS. In the Warsaw laboratory IgG positivity in SLE was revealed in 29%, in SLE+APS - in 33%, in primary APS - in 39%. in half of the pts IgG АСА level was doubtful or low-positive. Thromboembolic events were associated with the presence of IgG AB2 (mean level 0,292 U of OP, median 0,157, minimum - 0,049, maximum 0,994, interquartile dispersion 0,251). Mean level in the absence of thrombosis was 0, 178 U of OP (median 0,112, minimum - 0,440, maximum 0,834, interquartile dispersion 0,100), p=0,003 according to Mann-Whitney test. There was no statistical dependence between IgG АСА, IgG AAV and Ihrom- boembolic events but very high levels of antibodies were present in the group of pts with thromboses. There was a correlation between SLE activity and high AOLDPL level. Mean value of SLEDAI scale in 16 SLE pts with high AOLDPL level was 22,6+4,34 compared with 8,37+3,52 (p=0,000I) in 22 SLE pts not having these antibodies. Conclusion. Presence of IgG AB2 is associated with thromboses independently of their localization. Presence of AOLDPL was associated with disease activity.